Risk of hypoglycemia in hyperkalemia management with insulin among inpatients-experience in an acute care tertiary hospital - Siew Hoon Lim; Shin Yuh Ang; Siti Namira Binte Abdul Wahab; Ming Ming Teh; Fazila Aloweni (Proceedings of Singapore Healthcare)
Aim Hypoglycemia due to hyperkalemia treatment using intravenous insulin is a serious complication that affects patients’ safety. This study aimed to (i) describe the incidence rate of hypoglycemia and associated risk factors in adult patients who received hyperkalemia treatment and (ii) report the parameters of patients who experienced hypoglycemic episodes with corrected hyperkalemia and those without. Methods This prospective descriptive study included hospitalized patients between November 2020 and July 2022 who received intravenous insulin to treat acute hyperkalemia with serum potassium exceeding 5.0 to 5.5 mEq/L. Blood glucose monitoring was conducted 1, 2, 4, and 6 hours after treatment. Results Among 300 patients reviewed, the hypoglycemia rate was 19.7%; 78.6% of the hypoglycemic events occurred within the first 2 hours; 12.9% and 8.6% occurred at 4- and 6-hours post-treatment, respectively. One significant association with increased risk for hypoglycemia was a history of kidney-related conditions, including chronic kidney disease and undergoing hemodialysis or peritoneal dialysis. Among those who received the hyperkalemia treatment, 44.4% ( n = 133) had persistent uncorrected serum potassium readings, and 21.6% ( n = 29) experienced hypoglycemia episodes. Conclusions Hypoglycemia is a common complication associated with the use of intravenous insulin for hyperkalemia management in hospitalized patients, with a noted higher incidence in those with kidney-related conditions. Early monitoring within the first 2 hours after treatment is critical, as most hypoglycemic events occur during this period. Intensive blood glucose monitoring and standardized treatment protocols based on patient risk factors, such as renal history, are essential to enhance patient safety and minimize hypoglycemia.